2017
DOI: 10.1007/s00248-017-1123-7
|View full text |Cite
|
Sign up to set email alerts
|

Huanglongbing Control: Perhaps the End of the Beginning

Abstract: Huanglongbing (HLB) is one of the most destructive citrus plant diseases worldwide. It is associated with the fastidious phloem-limited α-proteobacteria 'Candidatus Liberibacter asiaticus', 'Ca. Liberibacter africanus' and 'Ca. Liberibacter americanus'. In recent years, HLB-associated Liberibacters have extended to North and South America. The causal agents of HLB have been putatively identified, and their transmission pathways and worldwide population structure have been extensively studied. However, very lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 142 publications
1
42
0
2
Order By: Relevance
“…However, identifying beneficial native endophytes from various citrus varieties under pathogen stress could possibly be used to control citrus pathogens and other plant pathogens. Similar trends has been reported regarding the devastating citrus disease, huanglongbing (HLB), which is caused by Candidatus Liberibacter asiaticus (CLas), Candidatus Liberibacter americanus, and Candidatus Liberibacter africanus 32 , resulting in severe losses to the citrus industry worldwide 33 . It has previously been shown that the restructuring of the citrus microbiome caused by HLB disease development could be overcome using native bacteria to manage the pathogen titer 34,35 .…”
supporting
confidence: 66%
“…However, identifying beneficial native endophytes from various citrus varieties under pathogen stress could possibly be used to control citrus pathogens and other plant pathogens. Similar trends has been reported regarding the devastating citrus disease, huanglongbing (HLB), which is caused by Candidatus Liberibacter asiaticus (CLas), Candidatus Liberibacter americanus, and Candidatus Liberibacter africanus 32 , resulting in severe losses to the citrus industry worldwide 33 . It has previously been shown that the restructuring of the citrus microbiome caused by HLB disease development could be overcome using native bacteria to manage the pathogen titer 34,35 .…”
supporting
confidence: 66%
“…The fastidious, phloem limited CLas bacterium cannot be cultured, preventing the completion of Koch's postulates and in vitro biological studies (Jagoueix et al, 1996;do Carmo Teixeira et al, 2005). Although short-term disease management using bactericides, plant immune activators, nutritional supplements, and heat treatments have been able to slightly reduce the acceleration of the citrus plant decline, the HLB pathogen shows vigorous strength against them and eventually overcomes these temporary therapies (Li et al, 2016;Blaustein et al, 2018;Munir et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Esta disminución provocó la caída del empleo, generando problemas sociales y deprimiendo la demanda de bienes y servicios en las zonas productoras de limón mexicano (Avalos y González, 2013). Los síntomas de esta enfermedad en México están asociados a la presencia de CLas, que es un parásito obligado, restringida al floema y que es diseminada eficientemente por el psílido asiático de los cítricos (Diaphorina citri) cuando se alimenta del floema, esta bacteria una vez dentro del árbol libera salicilato de metilo un químico volátil específico, que atrae a la población de insectos vectores para alimentarse del árbol infectado y así, es como el patógeno ingresa a mayor número de insectos, también CLas puede transmitirse de plantas de cítricos enfermas a sanas mediante injertos (Mann et al, 2012;Munir et al, 2017).…”
Section: Introductionunclassified